Tempered mlo broad-spectrum resistance to barley powdery mildew in an Ethiopian landrace - Ge, Cynthia; Deng, Weiwei; Lee, Zheng; Lopez-Ruiz, Fran; Schweizer, P.; Ellwood, Simon (Nature Publishing Group, 2016)
Recessive mutations in the Mlo gene confer broad spectrum resistance in barley (Hordeum vulgare) to powdery mildew (Blumeria graminis f. sp. hordei), a widespread and damaging disease. However, all alleles discovered to date also display deleterious pleiotropic effects, including the naturally occurring mlo-11 mutant which is widely deployed in Europe. Recessive resistance was discovered in Eth295, an Ethiopian landrace, which was developmentally controlled and quantitative without spontaneous cell wall appositions or extensive necrosis and loss of photosynthetic tissue. This resistance is determined by two copies of the mlo-11 repeat units, that occur upstream to the wild-type Mlo gene, compared to 11-12 in commonly grown cultivars and was designated mlo-11 (cnv2). mlo-11 repeat unit copy number-dependent DNA methylation corresponded with cytological and macroscopic phenotypic differences between copy number variants. Sequence data indicated mlo-11 (cnv2) formed via recombination between progenitor mlo-11 repeat units and the 3' end of an adjacent stowaway MITE containing region. mlo-11 (cnv2) is the only example of a moderated mlo variant discovered to date and may have arisen by natural selection against the deleterious effects of the progenitor mlo-11 repeat unit configuration.